Microambientes e sensores imunológicos no intestino: homeostase e inflamação - Maria Cecília Campos Canesso (2018)
The gut-associated lymphoid tissue faces the challenge of tolerating foreign nutrients and the symbiotic microbiome while excluding or eliminating gastrointestinal pathogens. Unregulated interactions between luminal antigens and the immune cells at the intestinal mucosa can lead to severe diseases such as food allergy, Celiac disease and inflammatory bowel diseases. This study addressed how immune responses in different gut microenvironments as well as their sensors affect intestinal homeostasis. We observed that the maintenance of intestinal homeostasis can be achieved in at least two different ways: through the compartmentalization of the specific immune responses to each distinct intestinal microenvironment, and by the immunological sensors of the components present in the intestinal environment. Herein we report that mesenteric lymph nodes (mLNs) are immunologically unique according to the functional gut segment they drain. Stromal and dendritic cell gene signatures as well as adaptive T cell polarization against the same luminal antigen differed between mLNs along the intestine, the proximal small intestine–draining mLNs preferentially giving rise to tolerogenic and the distal mLNs to pro-inflammatory T cell responses. This compartmentalized dichotomy could be perturbed by duodenal infection, surgical removal of select distal mLNs or ectopic antigen delivery, impacting immune responses. Regarding the perception of the intestinal environment, we show that STING, a cyclic dinucleotide sensor and adaptor molecule for intracellular DNA receptors, is also activated by microbiota products. The absence of STING leads to defective protective mechanisms of intestinal mucosa, such as lower mucus production and secretory IgA levels, altered frequencies of IELs and ILCs, besides impacting the composition of the intestinal microbiota toward a more pro-inflammatory profile. STING is also important for the development and function of Treg cells, being STING-/- mice more susceptible to colitis and enteric bacterial infection. Therefore, disorders of the intestinal microenvironments as well as the absence of these environments’ sensors, in this case of STING, influence the immune responses in these places and can lead to inflammatory conditions and higher susceptibility to diseases.